Whey Protein Hydrogels and Emulsion Gels with Anthocyanins and/or Goji Oil: Formation, Characterization and In Vitro Digestion Behavior - Abdullah S. Seddiek; Kaiwen Chen; Fanlin Zhou; Muhindo Mwizerwa Esther; Abdelaziz Elbarbary; Hazem Golshany; Angelo Uriho; Li Liang (Antioxidants)
Whey protein isolate (WPI) has functional properties such as gelation and emulsification. Emulsion gels combine the benefits of both emulsions and hydrogels. In this study, WPI hydrogels and emulsion gels were developed with goji oil (GO) as the oil phase by the inclusion of blueberry extract (BE) in the protein matrix. Heat-denatured WPI (hWPI) particles and emulsions were characterized in terms of size distribution, ζ-potential, interfacial protein, and anthocyanin partition. The inclusion of anthocyanins-rich blueberry extract led to the aggregation of hWPI particles, but it also increased the interfacial protein of 10% goji oil emulsions to 20% and decreased their size distribution to 120 and 325 nm. WPI hydrogels and emulsion gels were analyzed in terms of their water-holding capacity, which decreased from 98% to 82% with the addition of blueberry extract and goji oil. Syneresis, rheological, and morphological characteristics were also analyzed. The gelation time of hWPI particles and emulsions was shortened from 24 h to 12 h when incorporating blueberry extract to form a dense network. The network was the most homogeneous and densest in the presence of 3% blueberry extract and 5% goji oil. The co-inclusion of blueberry extract and goji oil increased the syneresis during the freeze–thaw cycles, with the values rising from 13% to 36% for 5% BE hydrogel and BE-containing emulsion gels after the first cycle. All WPI hydrogels and emulsion gels exhibit predominantly elastic behavior. Moreover, anthocyanin release, antioxidant activity, and the fatty acid composition profile were also analyzed during in vitro digestion. Soluble and free anthocyanins in the digested medium were reduced with the goji oil content but increased with the blueberry extract content. The stability of polyunsaturated fatty acids in the digested medium was improved by the addition of blueberry extract. The antioxidant activity of the digested medium increased with the content of blueberry extract but decreased with the content of goji oil. The ABTS∙+ scavenging capacities decreased from 63% to 49% by increasing the content of GO from 0% to 10% and they increased from 48% to 57% for 5% BE and 10% GO emulsion gels as the BE content increased from 0% to 5% after 6 h of digestion. The data gathered should provide valuable insights for future efforts to co-encapsulate hydrophilic and hydrophobic agents, thereby enhancing their stability, bioavailability, and functional properties for potential applications in food industries.